Remaining Reserves Drainage Optimization Using Infill Drilling Based on Subsurface Study Field - Ana Megawanti Haryuni; Erdila Indriani; Purnomosidi Purnomosidi (Indonesian Journal of Energy and Mineral, 2021)
The XY Field is an oil field in the Sunda Basin which was developed since 1981 and has been produced in the Baturaja carbonate layer and Talang Akar sandstone layer. Decreasing the amount of oil production in the reservoir can have a detrimental impact on the company so it is necessary to analyze the remaining reserves of the reservoir. The calculation used to evaluate the remaining reserves use the Volumetric, Material Balance and Decline Curve methods. From the three methods, the results that are close to the reserve of the XY field reservoir are 14 MMSTB. OOIP is obtained from the volumetric method and material balance which is divided into P10, P50 and P90. The reserve OOIP for P10 is 110.8 MMSTB and P90 is 60.34 MMSTB, with the last cumulative production in December 2019 being 9.3 MMSTB, where the economic limit of the field is 46 bbl. / day and the contract will be expired in 2038. From the results of the subsurface analysis, the four infill wells are candidates for infill wells because they have hydrocarbon potential. Then in terms of economics this development scenario is feasible to be developed with NPV reaching 9,140 MUSD, the ROR reaching 41% for PSC and 60% for Gross Split, and increases field recovery factor (RF) up to 56%.